Characterization of glucomannan from Amorphophallus panomensis in Vietnam - An, Nguyen Tien; Thien, Do Truong; Hoa, Nguyen Thi; Hue, Vu Thi; Minh Thu, Vu Thi; Thu Trang, Lai Thi (Vietnam Journal of Science and Technology, 2016)
A glucomannan has been isolated from the tuber of amorphophallus panomensis by a simple method without using toxic chemicals. The weight content of the glucomannan was about 4% of original amorphophallus tuber. The structure of the glucomannan was investigated by infrared (IR) and nuclear magnetic resonance spectroscopy (NMR). The results showed that the structural component of the glucomannan was consisted of mannose and glucose units with the mannose/glucose ratio was about 1.00/0.13. The degree of crystalation and molecular weight of the glucomannan were also investigated by XRD diffraction and viscosimetry, respectively. The results indicated that the glucomannan was amorphous and molecular weight was Mv = 1.2´106Da.